2-Dimensional Pressure Distribution in Saturated Petroleum Reservoir using Finite Difference - Adam Sukma Putra; Wahyu Srigutomo (Indonesian Journal of Physics, 2016)
The aim of this project is to solve the Darcy’s Equation using the finite difference (FD) method. We test the governing equation by investigating a saturated petroleum reservoir in two-dimensional (2-D) system to describe the distribution of the pressure within the reservoir. We assume that the velocity of the fluid (oil) is incompressible and relatively slow as a consequence that the system is saturated. The model used is a flow in steady state 2-D porous media. We apply the modified form of FN method with Gauss-Seidel to improve the precision of the simulation.